Longitudinal effects of task performance and self-concept on preadolescent EFL learners’ causal attributions of grammar success and failure - Faber, Günter (Studies in Second Language Learning and Teaching, 2019)
Learners’ academic self-concepts and attributions have been widely evidenced to substantially regulate their educational development. Developmentally, they will not only operate in a mutually reinforcing manner. Rather, self-concepts will directly affect learners’ outcome attributions in a particular academic setting. Current research in the English as a foreign language (EFL) context has increasingly analyzed learners’ attributions and self-concepts on a task-specific construct level. Nevertheless, there still exist certain research gaps in the field, particularly concerning learners’ grammar self-concept and attributions. Therefore, the present study aimed at analyzing longitudinal relations of prior performance and self-concept with subsequent attributions of grammar success and failure in a sample of preadolescent EFL learners. Findings demonstrated that attributional patterns mostly but not entirely depended on learners’ grammar self-concept. Poor performing learners holding a low self-concept displayed a maladaptive attribution pattern for explaining both grammar success and failure. Though not with respect to all causal factors, these findings largely confirm the crucial role of task-specific self-concept in longitudinally explaining related control beliefs in the EFL context.